Place attachment to waterfront revitalisation development : case study of Lumut and Kuching, Malaysia / Mohd Ismail Isa - Mohd Ismail, Isa (2017)
Urban development in Malaysia is inseparable from its existence, which began on the river banks. The design of river banks often changes with time and the level of urbanization. As a result, the physical environment of the river bank will indirectly affect the identity of the place. In fact, the revitalization that has been done able to establish the identity of the area. Relationship functional and emotional elements between human and place create meaning, this process is known as place attachment. Physical changes that occur results in a change of meaning and place attachment may decrease gradually. In the context of urban design, some discussions led to the physical element of interest and activity to develop place identity and atmosphere, but a study of open space areas have received less attention. The aim of this study is to verify the ability of place attachment and the factors that influence user’s perception in the context of open space on the waterfronts in Malaysia. Furthermore, to find out the cause (causal) between the places attachments, meaning the place and the characteristics that influence the level of public engagement. The objectives identified in this study are; (i) to determine the form of emotional and functional attachment of open space or place in the development of the waterfront; (ii) to identify the reasons that affect the place attachment especially on the meaning and importance of the place; (iii) to identify the level of place attachment with the user’s roles in the open spaces and; (iv) to identify the characteristics of open space along the waterfront, which influences by user’s engagement. A mixture of qualitative and quantitative approach are used in this research and covers two main areas of urban design and environmental psychology. Surveys and in-depth interviews conducted with users of selected two study areas, namely Kuching Waterfront (KW) in Sarawak and Lumut Waterfront (LW) in Perak. Observation’s also been used to obtain the physical and visual characteristics. The results showed that the place attachment is influencing users perception of public space at the river bank. Besides its physical quality, the place is also known for attachment and its significance to the user. Results from the study show several factors that influence the form and the level of engagement of the attachment, user familiarity with the place, place dependency, user background, and role. Therefore, this study contributes to human relationship with the place and give importance implications to urban planners, urban designers, and architects to create a better and well-organized place.